KONSELING KARIR RINGKAS BERFOKUS SOLUSI: KONSELING KARIR UNTUK MEMBANTU MENETAPKAN PILIHAN KARIR SISWA SMK MENGHADAPI MEA - Saputra, Wahyu Nanda Eka; Widiasari, Santi (JURNAL FOKUS KONSELING, 2017)
MEA be one challenge for the country of Indonesia. One way to prepare qualified human resources through education. The parties have a role to address the various challenges that arise and thrive in the world of education in Indonesia in the era of MEA is BK teacher/ counselor . Effective counseling interventions need to prepare qualified human resources in the face of the MEA , the Solution Focused Brief Career Counseling . In the counseling intervention , students are required to be able to immediately solve the problem of his career and making career choices that match their interests , talents and expertise so as to compete in the world of work.